CBT (Cognitive Behavior Therapy) Psychoeducational Intervention On Reducing Diabetes Distress Levels In Patients With Type 2 Diabetes: A Systematic Review - Syahrizal, Rofi; Sari, Anna Juwita Puspita; Sari, Vina Amelia Tunnikmah Desya Cournia (Griya Eka Sejahtera, 2024)
Background: Diabetes Mellitus Tpe 2 (T2DM) is a lifelong disease, while suffering from the disease patients will experience diabetes distress (DD) which causes negative emotions: anxiety, stress, depression. Cognitive Behavior Therapy (CBT) intervention helps patients in dealing with DD problems whose implementation does not require drug medication, in its implementation CBT has various sessions and each session has a different topic.Methods: This study used literature review and PRISMA method from 6 electronic databases (Cochrane Library, Ebsco Host, Proquest, PubMed, Sage Journal, Sciendirect, Scopus, Springer, Web Of Science.) n=4541, the search was conducted to find the effectiveness of CBT in reducing the level of DD in T2DM patients. Risk of bias was assessed using the Joanna Briggs Institute (JBI) critical appraisal tools checklist.Results: A total of 5 articles met the inclusion criteria of 5 articles with the Randomized Controlled Trial (RCT) method Respondents in the study were T2DM patients who were divided into 2 research groups (intervention and control). The results showed a difference in DD levels between the two groups.Conclusion: There is a significant effect on reducing the level of DD in patients with T2DM. The advantages of CBT intervention are not using pharmacological drugs, cost-effective, and easy to use. In addition, CBT intervention has the advantage that its flexible use can be adjusted to the needs and needs of the patients.